Oxidative stability of soybean oil added of purple onion (Allium cepa L.) peel extract during accelerated storage conditions - Umeda, Wellington Mamoro [UNESP]; Jorge, Neuza [UNESP] (Elsevier, 2021)
The onion (Allium cepa L.) is one of the most consumed vegetables worldwide and its peels present significant contents of flavonoids and bioactive compounds of high antioxidant capacity. The present work aimed to evaluate the effect of purple onion peel extract on the oxidative stability of soybean oil under oven accelerated storage. The soybean oil was added of the antioxidants: onion peels extract, tocopherol, ascorbyl palmitate and TBHQ (200 mg/kg), isolated or combiner (100 mg/kg of each antioxidant), and the treatments were subjected to accelerated storage conditions (60 °C/21 days). Samples were taken after 0, 7, 14 and 21 days and analyzed regarding the formation of oxidative compounds, both primary and secondary, and their tocopherol contents. Although TBHQ has shown higher efficacy in inhibiting oxidation, its combination with purple onion peel extract showed a synergistic effect. This combined condition retarded the appearance of degradation products and contributed to the total tocopherols retention over the storage. It highlights the potential use of natural extract for reducing the concentration of synthetic antioxidants to be applied in soybean oil.
Keywords: Accelerated storage; Antioxidant activity; Natural antioxidant; Phenolic compounds